2019
DOI: 10.1055/a-0927-6782
|View full text |Cite
|
Sign up to set email alerts
|

Resilienz bei langzeitüberlebenden Patienten mit einer Krebserkrankung – Zusammenhänge mit psychischer Belastung und soziodemografischen Merkmalen

Abstract: Zusammenfassung Einleitung Resilienz gilt als persönliche Ressource bei der Verarbeitung belastender und traumatischer Erfahrungen und findet in der psychoonkologischen Forschung zunehmend Beachtung. Ziel dieser Studie ist es, die Resilienz bei langzeitüberlebenden Krebspatienten in Abhängigkeit von Depressivität, Angst sowie soziodemografischen und krankheitsbezogenen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…There is a growing body of evidence that resilience can allow patients to adapt well to life after cancer and reduce their physical and psychological distress (Babić et al, 2020;Plitzko et al, 2020;Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing body of evidence that resilience can allow patients to adapt well to life after cancer and reduce their physical and psychological distress (Babić et al, 2020;Plitzko et al, 2020;Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies in various fields have shown that individuals who want to regain, sustain or improve their mental well‐being in contexts of adversity need to promote their resilience level (Ungar & Theron, 2020). There is a growing body of evidence that resilience can allow patients to adapt well to life after cancer and reduce their physical and psychological distress (Babić et al, 2020; Plitzko et al, 2020; Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%